Pedagogical and conflict situations of teacher of physical training - Pechko O.M (Kharkov National Pedagogical University, 2011)
The article reveals the essence of pedagogical and conflict situations between teacher and student. Considered ways of solving and preventing pedagogical and conflict situations in school. Principal reasons of conflict situations are selected, situations of activity, conduct and relations. The receptions of influence of teacher of physical culture are separated on personality of schoolchildren. It is well-proven that the profession of teacher of physical culture supposes possibility of conflict situations.